Pengunaaan Model Student Team Achievement Division terhadap Kemampuan Penalaran dan Pemecahan Masalah Matematis Siswa Kelas 1 SD - Shela Ayu Nadyarta; Moh Hadanil Atqo; Wido Rahayu Gondoarum; Muhammad Zidan Fakihani; Diana Ermawati (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Some grade 1 students still have difficulty counting without using an abacus. Many students who were creative and critical became apathetic because the learning atmosphere in the classroom was less supportive. Learning styles that are less democratic, less collaborative result in students being less active in learning activities in class. The aim of applying the STAD model is to improve the reasoning and mathematical solving abilities of elementary school students in low grades. This research uses a quantitative experimental method, the instruments used in this research are pre-test and post-test questions. Data collection techniques, researchers used observation, interviews, question sheets, and documentation. The data analysis technique that we use is parametric test with paired t-test. The results of the analysis show that the value of Sig. (2-tailed) is 0.000 <0.05, then Ho is rejected and Ha is accepted with a mean paired difference of -17.25000. This value shows the difference between the average pre-test learning outcomes and the average post-test learning outcomes, or 81.25-64.00 = -17.25000. So it can be concluded that there is an average difference between the learning outcomes of the Pre Test and Post Test, which means that there is an effect of using the STAD Learning model on increasing reasoning abilities and solving mathematical problems in 1st grade students of Elementary School.